Model for the assessment of quality of life: an analysis in telework or work at home conceptualized in Covid-19 times (Revista Torreón Universitario, 2022)
The work environment is, undoubtedly, a transcendental aspect in the life of everyone for its influence in social aspects, community participation, interpersonal relationships, individualistic and economic development, but, when becoming an obligation of partial type should not be a negative aspect, rather, comforting, with the purpose that the possible psychophysical coercion does not influence negatively in the quality of life. Therefore, the research aims to propose a model for assessing the quality of life of workers who are under telework or work at home, in addition to this, to promote a statistical model in R that facilitates the interpretation and analysis, with this, the company that performs it may formulate corrective approaches to improve the level of staff satisfaction, thus, performance and labor productivity. The methodology used corresponds to an initial reliability check with Cronbach's Alpha and to determine the path of the incident particularities we will use Classification and Regression Trees: CARTS. The results have been gratifying for the instrument, the level of reliability is in the ideal standard and the particularities indicate suitable coherence, the companies that seek to know the situationality of their workers in modality work at home or telework and, with this, to forge factors that influence in the continuous organizational improvement, it is important to emphasize that the instrument can be used in any type of organization without any discrimination.
Keywords: Decision trees; Quality of life; Covid-19; Job satisfaction; Telecommuting; Telework; Work at home